Antioxidant Effect of Centella asiatica Ethanolic Extract to Superoxide Dismutase (SOD) Level on Cyprinus carpio Liver - Diklawati Jatayu; Happy Nursyam; Asus Maizar Suryanto Hertika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
Centella asiatica is a herbal medicine has been used for many studies in some animals as antioxidant properties. This study was aimed to enhance the level of SOD in Cyprinus carpio after oral administration of C. asiatica extract. In the present study, phytochemical screening of bioactive constituents, antioxidant assay, and their effect on SOD in C. carpio liver were investigated. C. asiatica extract was obtained by maseration for 24 h using ethanol as a solvent. C. asiatica extract with 50, 100, 150 and 300 mg kg-1 body weight were administered every 3 days for two weeks. On the last day of experiment, fishes were killed and liver were removed from the body. The results showed that C. asiatica extract had some bioactive compounds such as flavonoid, alkaloid, terpenoid, tanin, saponin and DPPH scavenging activity with an IC50 value of 125 μg mL-1. C. asiatica extract also enhanced the level of SOD in fish liver. The SOD level was significantly difference compared to the control group with P<005. These results indicate that the ethanolic extract of C. asiatica had a potential antioxidant properties by scavenging free radical and enhancing the SOD level as antioxidant deffense inside the body.